IMPROVING THE MOTIVATION AND LISTENING ABILITY OF ELEVENTH GRADE STUDENTS BY USING SMART APP CREATOR - Yuri Susanti; Mulyadi Mulyadi; Indawan Syahri (Universitas PGRI Palembang, 2023)
The objective of this study was to find out and analyze the process of improving the motivation and listening ability of the eleventh grades students by using Smart App Creator in the Management Program at SMK Negeri 3 OKU Selatan. The method which used in this research is classroom action research where it took place in 3 cycles. The result of this study found that there was improvement of students’ listening ability and motivation. The score of minimum completeness criteria of English lesson was 70. In listening test cycle 1 there were 10 students who pass the minimum completeness criteria or 33,3% of students. In listening test cycle 2 there were 18 students who pass the minimum completeness criteria or 60% of students and in listening test of cycle 3 there were 26 students who pass the minimum completeness criteria or 86% of students. There were improvement of students listening ability as 52.7% where from cycle 1 to cycle 2 gained improvement as 26,7% and from cycle 2 to cycle 3 gained improvement as 26%. The students’ participation increased during the teaching learning process whereas it indicates the students’ motivation had increased. Faqih, (2021) have researched about Smart App Creator as a learning media where he found that smart app creator effective to use as a learning media of poetry lesson and now the researcher found that smart app creator can use as a learning media to improve students’ listening ability and motivation.